Sistem Keamanan Kunci Kontak Sepeda Motor Dengan Arduino Menggunakan Metode Bluetooth Pada Smartphone - Muhtajuddin Danny; Herdiana Herdiana (Jurnal SIGMA, 2021)
Motorbikes at this time are a means of transportation that are in great demand by various groups of people in Indonesia, from the middle to lower class to the upper middle class. Because vehicle ownership in Indonesia is not limited, therefore the number is very large in various provinces from Sabang to Merauke, one of which is Cikarang Kec. Selatan Kab. Bekasi, West Java Province. The number of people who own motorbikes in South Cikarang sub-district can be said to be large with various brands, types and models that offer various advantages, respectively. one of them is the security system on the motorcycle, the security system that the latest version of the motorcycle has is a smartkey However, there are still many motorbikes that do not have this feature, while the ignition is one of the weaknesses of motorbikes. The security system on the ignition of a motorcycle that is easily broken into by thieves, another cause of theft is user negligence or also known as human error. Therefore, a safety system for motorcycle contact locks is needed to prevent theft. In this study, the author intends to provide a solution to overcome the problem of motorcycle theft using an Arduino system that is connected to a smartphone.